1989
DOI: 10.1063/1.457624
|View full text |Cite
|
Sign up to set email alerts
|

Solvent influence on the magnetic field effect of polymethylene-linked photogenerated radical ion pairs

Abstract: The solvent viscosity and polarity dependence of the magnetic field effect in polymethylenelinked radical ion pairs, which were generated by photoinduced intramolecular electron transfer in compounds of the type pyrene-(CH2)n-N,N-dimethylaniline, has been studied. A stochastic Liouville equation is used, in which the dynamics of the polymethylene chain, the spin Hamiltonian as a function of the varying radical distance (exchange interaction), and a distance-dependent back electron transfer rate are incorporate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 28 publications
0
35
1
Order By: Relevance
“…In such RIPs having a long D-A distance, the exchange interaction may be so small that ISC from the singlet to the triplet states is reduced by H, as shown in solution [27,28] and at crystal surfaces [29]. Since the population of the singlet RIPs relative to that of the triplet RIPs becomes higher in the presence of H, exciplex fluorescence reduced by F is recovered to some extent in the presence of H; E-F-I-Q of the exciplex fluorescence becomes less in the presence of H. As already mentioned, it is also considered that fluorescent exciplex in type (I) is formed not only from RIP produced by PIET but also from a contact pair of the LE state, i.e., (D*…A) in Figure 1, since E-F-I-Q of the LE fluorescence, which leads to E-F-I-E of the number of RIPs produced by PIET, does not induce an enhancement of the exciplex fluorescence [61].…”
Section: Discussionmentioning
confidence: 99%
“…In such RIPs having a long D-A distance, the exchange interaction may be so small that ISC from the singlet to the triplet states is reduced by H, as shown in solution [27,28] and at crystal surfaces [29]. Since the population of the singlet RIPs relative to that of the triplet RIPs becomes higher in the presence of H, exciplex fluorescence reduced by F is recovered to some extent in the presence of H; E-F-I-Q of the exciplex fluorescence becomes less in the presence of H. As already mentioned, it is also considered that fluorescent exciplex in type (I) is formed not only from RIP produced by PIET but also from a contact pair of the LE state, i.e., (D*…A) in Figure 1, since E-F-I-Q of the LE fluorescence, which leads to E-F-I-E of the number of RIPs produced by PIET, does not induce an enhancement of the exciplex fluorescence [61].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the exchange energy ( J ) of these two electrons at HOMO and LUMO can be calculated by Equation : J=trueϕL(1)ϕH(2)(e2r1r2)ϕL(2)ϕH(1)dr1dr2where φ H and φ L represent the HOMO and LUMO wave functions, respectively; e is the electron charge. From Equation , it is clear that a small Δ E ST can be resulted via a small overlap integral of <φ H |φ L >, i.e., via spatial wave function separation of HOMO and LUMO …”
Section: Key Tadf Processesmentioning
confidence: 99%
“…Some contrasting conclusions have been reported for¯exibly linked radical pairs. Whereas Bittl and Schulten [52] found no di erence between distance-dependent and distance-inde pendent electron transfer, an observatio n which they assigned to the e ect that the stochastic motion averages the decay rates in the various conformations of the biradical to one e cient decay rate, Staerk et al [55] found it essential to use contact reaction behaviou r in order to reproduce the experimental results. This was not possible with distance independen t recombination.…”
Section: Introductionmentioning
confidence: 99%